2016 IEEE 16th International Working Conference on Source Code Analysis and Manipulation (SCAM) 2016
DOI: 10.1109/scam.2016.30
|View full text |Cite
|
Sign up to set email alerts
|

A Security Perspective on Code Review: The Case of Chromium

Abstract: Modern Code Review (MCR) is an established software development process that aims to improve software quality. Although evidence showed that higher levels of review coverage relates to less post-release bugs, it remains unknown the effectiveness of MCR at specifically finding security issues.We present a work we conduct aiming to fill that gap by exploring the MCR process in the Chromium open source project. We manually analyzed large sets of registered (114 cases) and missed (71 cases) security issues by back… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
3
1

Relationship

2
8

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 23 publications
0
25
0
Order By: Relevance
“…The authors' results indicate relatively low effectiveness in vulnerability detection. In line with these results, di Biase et al [30] found that approximately only 1% of Chromium's review comments are about potential security flaws. While these studies [27]- [30] mainly focus on the effectiveness of code review on vulnerability detection, our study investigates whether developers can(not) detect vulnerabilities (specifically IIV) during code review and the underlying causes with a focus on developers' knowledge and mindset.…”
Section: Re L a T E D Wo R Kmentioning
confidence: 82%
“…The authors' results indicate relatively low effectiveness in vulnerability detection. In line with these results, di Biase et al [30] found that approximately only 1% of Chromium's review comments are about potential security flaws. While these studies [27]- [30] mainly focus on the effectiveness of code review on vulnerability detection, our study investigates whether developers can(not) detect vulnerabilities (specifically IIV) during code review and the underlying causes with a focus on developers' knowledge and mindset.…”
Section: Re L a T E D Wo R Kmentioning
confidence: 82%
“…Thongtanunam et al [43] evaluated the impact that characteristics of MCR practices have on software quality, studying MCR practices in defective and clean source code files. Di Biase et al [22] analyzed the Chromium system to understand the impact of MCR on finding security issues, showing that the majority of missed security flaws relate to language-specific issues. However, these studies, as well as most of the current literature on contemporary code review, either focus on production files only or do not explicitly differentiate production from test code.…”
Section: Background and Motivationmentioning
confidence: 99%
“…Moreover, historical evidence provides several examples of individual cases that contributed to discovery in physics, economics, and social science (see "Five misunderstandings about case-study research" by Flyvjerg [20]). Even in the SE domain case studies of the Chromium project [14], [17], Apache case study by Mockus et al [42], and Mozilla case study by Khomh et al [26] have provided important insights. To promote building knowledge through families of experiments, as championed by Basili [5], we have made our dataset and scripts publicly available [48].…”
Section: Th R E a T S T O Va L I D I T Ymentioning
confidence: 99%